Coupling cobalt single-atom catalyst with recyclable LiBr redox mediator enables stable LiOH-based Li-O2 batteries - Kang Huang; Zhixiu Lu; Shilong Dai; Chunyu Cui; Nam Dong Kim; Huilong Fei (Materials Today Catalysis)
Cycling Li-O2 batteries (LOBs) via LiOH is promising for developing practically viable batteries, while promoting the formation and decomposition of LiOH remains a challenge. Cobalt single atom catalysts (Co-SACs) have been exploited to mediate the direct 4e− oxygen reduction reaction for generating LiOH discharge products, but their inferior oxygen evolution activity renders the battery low energy efficiency and poor cycling life. Herein, we for the first time introduce LiBr redox mediator (RM) into the Co-SACs-catalyzed LOB system to facilitate the decomposition of LiOH. In the discharge process, the catalysis of Co-SAC is unaffected with the presence of LiBr. During charging, Br3− is identified as the oxidizer to decompose LiOH at an appropriate potential (3.6 V). Significantly, the soluble Br−‬‬‬‬‬ is recyclable in the system as the BrO− intermediate‬‬‬‬‬‬‬‬‬‬ could shuttle to the anode and react with Li metal to regenerate Br−‬‬‬‬‬ ‬‬so that the generation of LiBrO3 deposit is circumvented‬‬‬‬‬‬‬‬. Consequently, the fabricated LOB demonstrates fewer side reactions, stable energy efficiency (drop rate of 0.10 % per cycle) and long cycle life (300 cycles at 1000 mA/g) under the ambient atmosphere.‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬